Construction of a preoperative emotional state and postoperative intra-abdominal pressure based prediction model for early enteral feeding intolerance in postoperative patients with gastric cancer - Xu, Yingying; Hu, Qiongyuan; Pei, Dandan; Zhang, Yin; Zhu, Huanhuan; Hui, Yan; Guan, Wenxian; Xu, Meiling; Chen, Li (Frontiers in Nutrition, 2024)
The incidence of enteral nutrition intolerance (ENFI) is high in patients after gastric cancer resection due to the characteristics of surgical traumatic stress and changes in the physiological structure of the digestive tract, and the current evaluation of ENFI mostly depends on the symptoms and complaints of patients , which is lagging and subjective. Accurate and objective prediction of the risk of early ENFI is critical to guide clinical enteral nutrition practice.This study included 470 patients who underwent radical gastric cancer surgery at the department of gastric surgery of a tertiary hospital in Nanjing, Jiangsu Province, between November 2021 and October 2022. The patients were divided into a training set (n=329) and a validation set (n=141) in a 7:3 ratio. The predictors were first screened through Lasso regression. Subsequently, multifactorial logistic regression analysis was used to establish a model for predicting patients' early ENFI column charts . Internal and external validation of the model were performed on the training set and validation set data, respectively, including plotting the area under the curve (AUC) of the receiver operating characteristic (ROC) curve and calibration curves to assess the differentiation and calibration of the prediction model. The incidence of early ENFI in postoperative patients with gastric cancer was 44.68% in the training set and 43.97% in the validation set. The final predictors entered into the model were enteral nutrition solution type (OR1=1.31/OR2=7.23), preoperative enteral nutrition pre-adaptation technique (OR=0.29), surgical approach (OR=2.21),preoperative Profile of Mood State-Short Form score (OR=5.07), and intra-abdominal pressure (OR=6.79). In the internal validation, the AUC was 0.836, the 95% CI ranged from 0.792 to 0.879, the Hosmer-Lemeshow test showed X2 =4.368 and P=0.737, the sensitivity was 0.775, and the specificity was 0.741. In the external validation, the AUC was 0.853, the 95% CI ranged from 0.788 to 0.919, the Hosmer-Lemeshow test showed X2 =13.740 and P=0.089, the sensitivity was 0.785, and the specificity was 0.823.The Nomogram model of early ENFI in postoperative patients with gastric cancer, had good predictive efficacy and may serve as a reference for healthcare professionals to identify high-risk patients with early ENFI after gastrectomy.